PENGEMBANGAN APLIKASI UJIAN BERBASIS KOMPUTER (COMPUTER BASED TEST) - Soleh Marifati, Imam; - UBSI, Ubaidillah (IJNS - Indonesian Journal on Networking and Security, 2020)
Abstract - The development of information technology today has developed rapidly. Including in the world of education. Computer-based learning and internet use have been widely used. Especially in 2020 where a covid-19 virus pandemic is occurring which forces online teaching and learning activities from students' homes, the use of the internet in learning (e-learning) is increasingly needed. One of the uses of information technology to support learning activities is a computer-based test (CBT) can be implemented in schools. Using this method, the online learning process can be made easier, because it can be accessed by students from home. CBT can be used as a complement to online learning conducted by teachers such as the use of video conferencing such as Zoom applications, Youtube channels and others. In addition, implementation costs can be saved because schools no longer use stationery. CBT also makes it easy for teachers to correct student answers, even exam results can be assessed instantly when students finish working on questions. Whereas students will find it easy to answer, simply by clicking on the correct answer choice so that the use of time is more effective. In this research, a CBT application was developed that can be implemented by those who need it, especially schools. The application is built using web technology so that it is easy to run from various devices or platforms. Application access can be designed for use on a local (intranet) or online network by hosting the application on a webserver. The application development uses a system development life cycle approach. Keyword : Computer base test, CBT, webapps, intranet. Abstrak - Perkembangan teknologi informasi dewasa ini telah berkembang pesat. Termasuk juga dalam dunia pendidikan. Pembelajaran berbasis komputer maupun penggunakan internet telah banyak digunakan. Terlebih pada tahun 2020 ini di mana terjadi pandemi virus covid-19 yang memaksa kegiatan belajar-mengajar dilakukan secara daring dari rumah siswa, penggunaan internet dalam pembelajaran (e-learning) semakin dibutuhkan. Salah satu penggunaan teknologi informasi untuk mendukung kegiatan belajar adalah ujian (test) berbasis komputer atau computer based test (CBT) dapat diimplementasikan di sekolah. Dengan menggunakan metode ini, proses pembelajaran daring dapat dipermudah, karena dapat diakses oleh siswa dari rumah. CBT dapat digunakan sebagai pelengkap pembelajaran daring yang dilakukan oleh guru seperti penggunaan video conferece seperti aplikasi Zoom, channel Youtube dan lainnya. Selain itu, biaya pelaksanaan dapat dihemat karena sekolah tidak lagi menggunakan alat tulis. CBT juga memudahkan guru dalam mengoreksi jawaban-jawaban siswa, bahkan hasil ujian dapat dinilai seketika saat siswa selesai mengerjakan soal-soal. Sedangkan bagi siswa akan mendapat kemudahan dalam menjawab, cukup dengan mengklik pilihan jawaban yang benar sehingga penggunaan waktu lebih efektif. Dalam penelitian ini, dikembangkan aplikasi CBT yang dapat diimplentasikan oleh pihak-pihak yang membutuhkan khususnya sekolah. Aplikasi dibangun menggunakan teknologi web sehingga mudah dijalankan dari berbagai perangkat atau platform. Akses aplikasi dapat dirancang untuk penggunaan jaringan lokal (intranet) maupun online dengan meng-host aplikasi pada webserver. Adapun pengembangan aplikasi menggunakan pendektan siklus hidup pengembagan sistem (system develompent life ecycle). Keyword : Test berbasis komputer, CBT, aplikasi web, intranet.